The Influence of Boiled Water Green Sirih Leaves Against Perineum Wound in Public Mother at BPM Bidan Desy Astuti Tangerang in 2022 - Nurzzanah, Siti (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Improper perineal care can lead to postpartum infection. Perineal injury is a wound that resulted from an episiotomy. Traditionally, perineal wound management uses boiled green betel leaf water to accelerate the healing of perineal wounds. This study aims to determine the effect of boiling green betel leaf water on perineal wounds in postpartum mothers at BPM bidan Desy Astuti in tangerang Regency in 2022. This study used a quesi-experimental research design with a two group pretest posttest design. The research sample consisted of 30 respondents. The sampling technique used total sampling. The instrument used was the observation sheet. The bivariate analysis test used the wilcoxon sign rank test. Based on the results of the wilcoxon sign rank test, the pretest group score was 0.001 and the posttest group score was 0.005. Both groups have a p value <0.05, which means that there is a difference in REEDA scores between the intervention group and the control group. Based on the results of the man Whitney test, the value of sig = 0.000 in the variable of perineal wound healing with boiled greed betel leaf water, it can be concluded that “Ha is accepted” (Sig. 0.000 <0.05) This means that there is an effect of giving boiled green betel leaf water on perineal wounds in postpartum mother in BPM midwife Desy astute in Tangerang Regency in 2022. There is a significan effect on the provision of green betel leaf water decoction on pperineal wound healing in post partum mothers.